Trade Facilitation in the Caucasus : Final Report - World Bank (Washington, DC, 2013)
From 15 May to 2 June 2000 COWI conducted a mission to the three Caucasian republics of Azerbaijan, Georgia and Armenia, spending about one week in each country. The mission established an initial overview of trade facilitation issues and conducted an outline Trade Facilitation Audit for the region. The purpose of the mission was to prepare for possible progress towards the re-opening of borders in the region, in the event that a peace agreement is reached in Nagorno-Karabakh. This chapter commences by summarizing some of the most interesting facts, relating to the movement of a generic consignment in the Caucasus region, which emerged from the discussions with stakeholders during the mission. Section 1.2 addresses what can be considered the key issue of the study; namely, whether, in the event of peace, the region would realize the maximum potential benefit, given the current institutional and operational context. A subsidiary issue is whether all the constituent countries in the region would benefit, or whether some would suffer some initial dis-benefits. The final section of this chapter provides a summary of the key regional and national recommendations, which have been identified to try and ensure that the potential benefits of any settlement are not dissipated in the current institutional and operational mire. A more detailed breakdown of the provisional recommendations, by component and sub-component, together with an estimate of the required inputs, is provided in Appendix B.